2005
DOI: 10.1116/1.1894417
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled quantum-dot molecules by molecular-beam epitaxy

Abstract: Articles you may be interested inGrowth by molecular beam epitaxy of self-assembled InAs quantum dots on InAlAs and InGaAs lattice-matched to InP High-temperature operation of self-assembled Ga In N As ∕ Ga As N quantum-dot lasers grown by solid-source molecular-beam epitaxy Self-assembled InAs quantum-dot ͑QD͒ molecules having high dot density and aligned dot set structure, which is defined by nanotemplates, were realized by thin capping and regrowth technique in a molecular-beam epitaxy process. Thin capping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Lateral QDMs have been achieved by several growth techniques, such as a combination of in situ etching and self-assembly [9] and self-assembly by anisotropic strain engineering on an In(Ga)As/GaAs (311B) superlattice (SL) template [10]. In our previous work, lateral QDMs have also been obtained using a thin-capping-and-regrowth technique by solid-source molecular beam epitaxy (SSMBE) under As 4 overpressure [11]. After isolated selfassembled QDs are capped partially with GaAs, nanoholes (camel-like nanostructure) are formed.…”
Section: Introductionmentioning
confidence: 98%
“…Lateral QDMs have been achieved by several growth techniques, such as a combination of in situ etching and self-assembly [9] and self-assembly by anisotropic strain engineering on an In(Ga)As/GaAs (311B) superlattice (SL) template [10]. In our previous work, lateral QDMs have also been obtained using a thin-capping-and-regrowth technique by solid-source molecular beam epitaxy (SSMBE) under As 4 overpressure [11]. After isolated selfassembled QDs are capped partially with GaAs, nanoholes (camel-like nanostructure) are formed.…”
Section: Introductionmentioning
confidence: 98%
“…The shortening of nanopropeller blades leads to lower number of satellite dots per QDM, i.e. from 10-12 dots per QDM to 6-8 and 4-5 dots per QDM, respectively [13,14]. In this report, we extend our work to study the effect of capping thickness while keeping the whole processing temperature constant at 470 1C.…”
Section: Sample Preparationmentioning
confidence: 75%
“…Another approach is based on a quantum mechanical property, a spin, of electrons in semiconductors [12]. In this paper, we study how to control dot number in QDMs by varying several growth parameters of thin-capping-andregrowth MBE process [13,14]. In addition, anisotropic strain during thin capping of initial QDs gives rise to elongated nanostructure along ½11 0 crystallographic direction.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral quantum dot molecules can be realized by several growth techniques (R. Songmuang et al, 2003. The thin-capping-and-regrowth molecular beam epitaxial process, which can be used to obtain quantum dot molecules in one continuous growth, has been demonstrated (S. Suraprapapich et al, 2005). Multiple cycles of the thin-capping-and-regrowth process of the quantum dots give improved dot alignment www.intechopen.com up to a certain number of growth cycles.…”
Section: Quantum Dot Moleculesmentioning
confidence: 99%
“…In order to obtain aligned dots, many approaches have been proposed and demonstrated (Z. M. Wang et al, 2004, Z. M. Wang et al, 2004, but those based on self-assembly are preferred over other techniques due mainly to the simplicity of the processes involved. It has been demonstrated that thin capping of quantum dots provides anisotropic strain fields which lead to the elongation of capped nanostructures after annealing (S. Suraprapapich et al, 2005). The regrowth of quantum dots on elongated nanostructures results in aligned quantum dots and aligned quantum dot molecules (QDMs).…”
Section: Quantum Dot Moleculesmentioning
confidence: 99%